Comparative study of safety and efficacy of electrocautery blade with cold scalpel blade for skin opening during fixation of fracture of forearm bone with plate and screws (Health Renaissance, 2017)
Background: Skin incisions have usually been made using a scalpel. Electrocautery, a more recent alternative, is thought to increase the risk of infection, impair healing and decrease cosmesis. Recent studies suggest that electrocautery may offer potential advantages with respect to blood loss, incision time and postoperative pain.Objective: The aim of this study was to compare the efficacy and safety of electrocautery incisions versus conventional scalpel incisions in orthopedic surgeries using internal implants.Method: The study was conducted as a prospective one in a tertiary care center in the Department of Orthopaedics, BPKIHS, Dharan, Nepal. Patients with closed fracture of the forearm bones admitted for surgery from April 2014 to September 2014 was included in the study. Each incision was divided into two halves, proximal half to be opened by steel scalpel blades and the distal half to be opened by an electrocautery blade. Proximal half and distal half of incision were compared on operating day and on days 2, 14 and again on 6 weeks and 3 month.Result: A total of 60 patients were enrolled in the study. Forearm skin incisions using electrocautery were significantly quicker than scalpel incisions (p0.05).Conclusion: There is no difference in healing of two halves of skin incision made by electrocautery and scalpel in orthopedic surgeries using internal implants.Health Renaissance 2015;13(2): 43-49